“Everywhere We Go, People Seem to Know”: Mad Students and Knowledge Construction of Mental Illness in Higher Education - Carette, Lieve (2018)
Psychological wellbeing has received attention from academics and policymakers worldwide. Initiatives to improve psychoeducation, campaigns to raise awareness, and charity projects have been established as part of efforts to change public attitudes and behaviors toward mental health problems. The common goal of these initiatives is the prevention of mental health problems in order to reduce the global burden of mental health disease. Some target groups have benefited from such initiatives. However, little attention has been paid to side effects—including harm—of widespread knowledge sharing that is not accompanied by appropriate action. Young adults may be less afraid than older adults to disclose mental health illness and share their lived experiences of mental health. Like older adults, students try to protect their autonomy and privacy in disclosing mental health problems and associated diagnoses. However, many young adults view self-disclosure as a request for help. Confronted with rising demand to support students’ psychological well-being, many higher education providers have launched initiatives to improve students’ knowledge about mental illness. Instead of making assumptions about what students need to know in order to improve their overall psychological wellbeing, we asked ‘Mad students’ (that is, students who identify as mentally ill) about their knowledge construction and management of mental illness. Analyzing this process highlights that mental health promotion is more complicated than sharing appropriate information or applying effective strategies. Knowledge sharing has improved public knowledge of mental illness. However, mental health promotion that omits simple communication about expectations and needs around mental health, to co-produce a shared knowledge base, may lead to misunderstanding and failure in meeting the needs of target groups.